STUDI KASUS: KONSELING LAKTASI PADA IBU POSTPARTUM UNTUK MENINGKATKAN BERAT BADAN BAYI - Arvicha Fauziah; Kasmiati Kasmiati (Poltekkes Kemenkes Maluku, 2022)
Neonates are newborns up to 28 days old, where there is a very big change from life inside the womb to outside the womb. Lactation counseling is most effective for increasing exclusive breastfeeding in infants. The success of exclusive breastfeeding cannot be separated from being influenced by several factors including age, level of education, experience and husband's support. Mothers who give birth for the first time do not have health information about breastfeeding, so midwives need to conduct lactation counseling. Lactation counseling about exclusive breastfeeding, how to care for breasts and proper breastfeeding techniques. This case study describes the management of midwifery care for Mrs. A, a 20-year-old primipara, who was confused about caring for a baby after giving birth. Handling efforts are carried out with a lactation counseling and guidance approach. Case studies use assistive devices in the form of a midwifery care format for normal newborns and status sheets or patient documentation and a list of interview questions. Data analysis used is data reduction, data presentation and conclusion. The result of the case study was that Mrs. A's baby's weight increased by 550 grams for 14 days after being given lactation counseling and breastfeeding guidance. Comprehensive midwifery care provided increases mothers' understanding of newborn care.